Three new species of Promicrogaster Brues & Richardson (Hymenoptera: Braconidae) from India - Ranjith, A.p.; Fernandez-Triana, Jose; Sushama, V.; Rajmohana, K.; Priyadarsanan, Dharma Rajan (Zootaxa, 2024)
The Indian fauna of the microgastrine genus Promicrogaster is reviewed and three new species are described: P. constricta, P. flava, and P. incompleta, all authored by Ranjith & Fernandez-Triana. Until now only one species had been reported from India. An illustrated key for the Oriental region, including all previously described species, is also provided.